PEMANFAATAN UNSUR LOKAL DALAM RAGAM BAHASA IKLAN - Sriyanto NFN (Balai Bahasa Provinsi Papua, 2019)
In this modern era advertising is an integral part of everyday life. Almost every need of our lives marketed with these ads. Efforts were made for an interesting ad. This study aims to determine whether the ad utilizes local elements that created an interesting ad. Then be studied also the type or kind of local elements are used in the creation of ads. Therefore, this research uses descriptive analysis method by observation techniques in the field data collection. Data collected either through direct observation in the field and through the television media. The result showed that many ads that take advantages of local elements in making its ads. Local elements in the form of accent or dialect and can also be the local language.